Non-isocyanate polyurea and preparation method thereof, water-based non-isocyanate polyurea and preparation method thereof, and anticorrosive paint, waterproof paint and fireproof paint containing water-based non-isocyanate polyurea
The preparation of non-isocyanate polyurea through alkali metal alkoxide/ionic liquid composite catalyst system has solved the problems of incomplete reaction and poor performance of aqueous polyurea in the prior art, and achieved a non-isocyanate polyurea with high reaction rate and excellent mechanical properties. Used to prepare coatings with excellent corrosion resistance, water resistance and fire resistance.
Patent Information
- Application Number
- CN202411259532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
The existing non-isocyanate polyurea synthesis methods have incomplete reactions, many side reaction products, which affect product quality, and the comprehensive performance of the aqueous polyurea coating film is poor, which limits its application and development.
The alkali metal alkoxide/ionic liquid composite catalyst system is used to prepare non-isocyanate polyurea by reacting polyetheramine with carbon dioxide to improve the reaction rate, and add an emulsifier under dispersion conditions to prepare aqueous non-isocyanate polyurea for the preparation of anti-corrosion and waterproof , fire-retardant coating.
It achieves high reaction rate and excellent mechanical properties of non-isocyanate polyurea. The coating has good corrosion resistance, water resistance and long service life. The coating has excellent substrate adhesion and fire resistance.
Smart Images

Figure BDA0005035613150000031 
Figure BDA0005035613150000041 
Figure BDA0005035613150000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of non-isocyanate polyurea products, and specifically, to a non-isocyanate polyurea and a preparation method thereof, a water-based non-isocyanate polyurea and a preparation method thereof, an anti-corrosion coating comprising the non-isocyanate polyurea, a waterproof coating comprising the non-isocyanate polyurea, a water-based polyurea-based intumescent steel structure fire retardant coating comprising the water-based non-isocyanate polyurea, and a transparent finishing type fire retardant coating comprising the water-based non-isocyanate polyurea. Background Art
[0002] Polyurea (PUR for short) is a polymer containing a repeated urea bond structure, and its mechanical properties can vary from elastic to rigid, and it has excellent comprehensive properties such as wear resistance, anti-skid, corrosion resistance and strength. At present, polyurea is mainly obtained by reacting the prepolymer of isocyanate with amine substances. However, isocyanate has strong irritation and toxicity, and the raw material for preparing isocyanate is also the highly toxic substance phosgene, which is extremely harmful to the human body and the environment. With the advocacy of "green chemistry", the preparation of non-isocyanate polyurea (NIPUR) using non-toxic and environmentally friendly raw materials has become a research hotspot at this stage, and the gradual replacement of traditional polyurea by NIPUR is an inevitable trend for the future development of the polyurea industry.
[0003] At present, there are few reports on the synthesis of non-isocyanate polyurea (NIPUR) in China. The existing synthesis methods often result in incomplete reactions and are accompanied by many side reaction products, which seriously affect the product quality and greatly limit the application and development of NIPUR.
[0004] In addition, as the public's requirements for environmental protection become more urgent and strict, in the field of new chemical materials, the preparation process of polymer resins is gradually shifting from solvent-based to water-based. As a new type of water-based polymer, water-based polyurea has been a hot topic in the research of polyurea coatings in recent years. Water-based polyurea has the advantages of simple construction operation, low cost, and more practical products. It uses water as a dispersion medium and meets the requirements of environmental protection regulations. However, it still faces some problems such as poor comprehensive performance of the coating, poor water resistance of the coating, and low gloss, which to a certain extent restricts the development of water-based polyurea.
[0005] Therefore, the field of water-based polyurea urgently needs to develop a product with high physical properties, excellent coating water resistance and long service life so as to be applied in a wider range of fields, thereby promoting the application and development of water-based polyurea.
[0006] As the main component of coatings, film-forming substances are mainly used to firmly adhere the coatings to the surface of materials and form a continuous coating film. Therefore, the performance of film-forming substances determines the performance of coatings. At present, coating products with traditional resins (such as polyurethane, epoxy resin or acrylic resin) as film-forming substances are limited by the physical and chemical properties of the resins themselves, which greatly restricts the application and development of anti-corrosion coatings, waterproof coatings and fire-retardant coatings.
[0007] Therefore, the coatings industry is in urgent need of developing coatings products with high physical and chemical properties and long service life to promote the application and development of coatings products. Summary of the invention
[0008] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a non-isocyanate polyurea and a preparation method thereof, and a derivative product containing the non-isocyanate polyurea. The non-isocyanate polyurea process according to the present invention is simple and has a high reaction rate. When the water-based non-isocyanate polyurea is used as a raw material to prepare water-based non-isocyanate polyurea, the coating mechanical properties (including tensile strength, elongation at break, and tear strength) are excellent; and when the non-isocyanate polyurea is used as a film-forming substance to prepare an anti-corrosion coating, the resulting coating has excellent corrosion resistance, high physical properties and a long service life; and when the non-isocyanate polyurea is used as a film-forming substance to prepare a waterproof coating, the resulting coating has good elongation at break, tensile strength and tear strength; and when the water-based non-isocyanate polyurea prepared from the non-isocyanate polyurea is used as a film-forming substance to prepare an intumescent steel structure fire retardant coating and a transparent finishing type fire retardant coating, the resulting coating has excellent fire resistance, good water resistance and excellent bonding strength.
[0009] In order to achieve the above technical purpose, the technical solution adopted by the present invention is as follows:
[0010] According to one aspect of the present invention, there is provided a method for preparing a non-isocyanate polyurea, the method comprising the following steps:
[0011] (1) mixing an alkali metal alkoxide and an ionic liquid to obtain an alkali metal alkoxide / ionic liquid composite catalyst; and
[0012] (2) In the presence of the alkali metal alkoxide / ionic liquid composite catalyst, a polyetheramine is mixed with an organic solvent, and then carbon dioxide is introduced to react to obtain the non-isocyanate polyurea, wherein the polyetheramine is an amino-terminated polyoxypropylene diamine or an amino-terminated polyoxypropylene triamine having a number average molecular weight in the range of 230 to 5000.
[0013] According to certain preferred embodiments of the present invention, the alkali metal alkoxide is selected from one or more of sodium methoxide, sodium tert-butoxide, lithium tert-butoxide, potassium tert-butoxide and sodium ethoxide.
[0014] According to certain preferred embodiments of the present invention, the ionic liquid is an imidazolium acetate ionic liquid, a pyridinium acetate ionic liquid or a combination thereof.
[0015] According to certain preferred embodiments of the present invention, the ionic liquid is selected from one or more of 1,3-dimethylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-propyl-3-methylimidazolium acetate, 1-pentyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-hexyl-3-methylimidazolium acetate, 1-heptyl-3-methylimidazolium acetate, 1-octyl-3-methylimidazolium acetate, 1-decyl-3-methylimidazolium acetate, 1-ethyl-2,3-dimethylimidazolium acetate, 1-butyl-2,3-dimethylimidazolium acetate, N-ethylpyridine acetate and N-butylpyridine acetate.
[0016] According to certain preferred embodiments of the present invention, the organic solvent is one or more of xylene, acetone, ethyl acetate and ethylene glycol dimethyl ether.
[0017] According to certain preferred embodiments of the present invention, the number average molecular weight of the amino-terminated polyoxypropylenediamine is in the range of 230 to 4,000.
[0018] According to certain preferred embodiments of the present invention, the number average molecular weight of the amino-terminated polyoxypropylene triamine is in the range of 440 to 5,000.
[0019] According to certain preferred embodiments of the present invention, the number average molecular weight of the non-isocyanate polyurea is in the range of 50,000 to 600,000, preferably 200,000 to 350,000.
[0020] According to certain preferred embodiments of the present invention, the amino-terminated polyoxypropylenediamine has a structure represented by the following general formula (1):
[0021]
[0022] Where n is the degree of polymerization.
[0023] According to certain preferred embodiments of the present invention, the amino-terminated polyoxypropylene triamine has a structure represented by the following general formula (2):
[0024]
[0025] Where a, b and c are the degrees of polymerization.
[0026] According to certain preferred embodiments of the present invention, in step (1), under the protection of an inert gas, an alkali metal alkoxide and an ionic liquid are mixed at room temperature to obtain an alkali metal alkoxide / ionic liquid composite catalyst.
[0027] According to certain preferred embodiments of the present invention, in step (1), the weight ratio of the alkali metal alkoxide to the ionic liquid is in the range of 1:5 to 1:20.
[0028] According to certain preferred embodiments of the present invention, in step (2), the ratio between the weight of the alkali metal alkoxide / ionic liquid composite catalyst and the weight of the polyetheramine is 1×10 -5 : 1 to 1×10 -3 : within the range of 1.
[0029] According to certain preferred embodiments of the present invention, in step (2), the reaction temperature is 150-190° C., the reaction pressure is 10.6-23.5 MPa, and the reaction time is 6-11 h.
[0030] According to another aspect of the present invention, a non-isocyanate polyurea is provided. The non-isocyanate polyurea is prepared according to the above method.
[0031] According to certain preferred embodiments of the present invention, the non-isocyanate polyurea is an amine-terminated linear polymer.
[0032] According to certain preferred embodiments of the present invention, the non-isocyanate polyurea is an amine-terminated branched polymer.
[0033] According to another aspect of the present invention, there is provided a method for preparing a water-based non-isocyanate polyurea, the method comprising the following steps:
[0034] (1) preparing a non-isocyanate polyurea according to the preparation method described above;
[0035] (2) Under dispersion conditions, an emulsifier is added to the non-isocyanate polyurea prepared in step (1), and then water is slowly added to obtain a water-based non-isocyanate polyurea.
[0036] According to certain preferred embodiments of the present invention, the emulsifier in step (2) is a polyoxyethylene ether emulsifier.
[0037] According to certain preferred embodiments of the present invention, in step (2), the amount of the emulsifier added is 2-10% by weight, based on 100% by weight of the non-isocyanate polyurea.
[0038] According to certain preferred embodiments of the present invention, the ratio of the weight of the non-isocyanate polyurea to the weight of the added water in step (2) is in the range of 1:1 to 1:5.
[0039] According to another aspect of the present invention, a non-isocyanate polyurea anti-corrosion coating is provided, which comprises: 50-80 parts by weight of the non-isocyanate polyurea prepared according to the preparation method described above, 10-30 parts by weight of titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoamer, 0.3-1.0 parts by weight of an ultraviolet absorber and 2-20 parts by weight of a solvent.
[0040] According to certain preferred embodiments of the present invention, in the non-isocyanate polyurea anticorrosive coating:
[0041] The titanium dioxide is rutile titanium dioxide; and / or
[0042] The defoamer is a polyolefin solution defoamer; and / or
[0043] The dispersant is a polyphosphate wetting dispersant; and / or
[0044] The ultraviolet absorber is a benzotriazole ultraviolet absorber; and / or
[0045] The solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate and xylene.
[0046] According to another aspect of the present invention, a non-isocyanate polyurea waterproof coating is provided, comprising: 25-43 parts by weight of the non-isocyanate polyurea prepared according to the preparation method described above, 20-28 parts by weight of a plasticizer, 25-36 parts by weight of a filler, 0.1-0.5 parts by weight of a defoamer and 3-11 parts by weight of a solvent.
[0047] According to certain preferred embodiments of the present invention, in the non-isocyanate polyurea waterproof coating:
[0048] The plasticizer is one or more of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, trioctyl phosphate, citrate and chlorinated paraffin plasticizers; and / or
[0049] The filler is one or more of rutile titanium dioxide, kaolin, heavy calcium carbonate, barium sulfate, magnesium oxide, calcium oxide, wollastonite and talc; and / or
[0050] The defoamer is a polyolefin solution defoamer; and / or
[0051] The solvent is one or more of xylene, solvent oil, ethyl acetate, butyl acetate and propylene glycol methyl ether acetate.
[0052] According to another aspect of the present invention, there is provided a water-based non-isocyanate polyurea-based intumescent fire retardant coating for steel structures, wherein the water-based polyurea-based intumescent fire retardant coating for steel structures comprises: 25-35 parts by weight of a water-based non-isocyanate polyurea prepared according to the preparation method described above, 0.1-1 parts by weight of a defoamer, 0.5-1 parts by weight of a dispersant, 0.1-0.5 parts by weight of a pH regulator, 5-20 parts by weight of titanium dioxide, 6-15 parts by weight of melamine, 6-15 parts by weight of pentaerythritol, 20-30 parts by weight of ammonium polyphosphate, 0.3-1 parts by weight of a thickener and 10-25 parts by weight of water.
[0053] According to certain preferred embodiments of the present invention, in the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating:
[0054] The defoamer is a composite silicone defoamer; and / or
[0055] The dispersant is an aqueous solution of modified styrene maleic anhydride copolymer; and / or
[0056] The pH regulator is an aqueous solution of reactive organosilicon; and / or
[0057] The titanium dioxide is rutile titanium dioxide; and / or
[0058] The thickener is a polyurethane modified polyether associative thickener.
[0059] According to another aspect of the present invention, there is provided a water-based non-isocyanate polyurea-based transparent finishing fire-retardant coating, which comprises: 25-35 parts by weight of a water-based non-isocyanate polyurea prepared according to the preparation method described above, 0.1-1 parts by weight of a defoamer, 0.1-0.3 parts by weight of a pH adjuster, 8-15 parts by weight of a polyol, 20-30 parts by weight of ammonium polyphosphate, 8-15 parts by weight of a water-based amino resin, 0.5-1 parts by weight of a thickener and 10-25 parts by weight of water.
[0060] According to certain preferred embodiments of the present invention, in the water-based non-isocyanate polyurea-based transparent finishing type fire retardant coating:
[0061] The defoamer is a composite silicone defoamer; and / or
[0062] The pH regulator is an aqueous solution of reactive organosilicon; and / or
[0063] The polyol is selected from one or more of sorbitol, xylitol and maltitol; and / or
[0064] The ammonium polyphosphate is a short-chain low-polymerization ammonium polyphosphate that is completely soluble in water; and / or
[0065] The water-based amino resin is a methyl etherified melamine amino resin; and / or
[0066] The thickener is a polyurethane modified polyether associative thickener.
[0067] Compared with the prior art in this field, the advantages of the present invention are:
[0068] 1) Non-isocyanate polyurea was prepared by a simple process route using an alkali metal alkoxide / ionic liquid composite catalyst system;
[0069] 2) The non-isocyanate polyurea according to the present invention has a high reaction rate, excellent mechanical properties (including tensile strength, elongation at break, tear strength), and good chemical corrosion resistance;
[0070] 3) The water-based non-isocyanate polyurea prepared according to the non-isocyanate polyurea of the present invention has a coating film with higher physical properties, such as tensile strength, elongation at break and tear strength;
[0071] 4) The non-isocyanate polyurea anticorrosive coating according to the present invention has excellent substrate adhesion and corrosion resistance (e.g., acid resistance, salt water resistance, salt spray resistance, and artificial aging resistance, etc.);
[0072] 5) The non-isocyanate polyurea waterproof coating according to the present invention has good elongation at break, tensile strength, tear strength and a long service life;
[0073] 6) The water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating according to the present invention has high fire resistance, water resistance and solid content; and
[0074] 7) The water-based non-isocyanate polyurea-based transparent finishing fire retardant coating according to the present invention has high fire resistance, bonding strength and good decorative properties. DETAILED DESCRIPTION
[0075] The present invention will be described in further detail below in conjunction with specific embodiments. It will be appreciated that other embodiments are contemplated and may be implemented without departing from the scope or spirit of the present invention. Therefore, the following detailed description is non-restrictive.
[0076] Unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physicochemical properties should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0077] At present, there are few studies on non-isocyanate polyurea, and the known non-isocyanate polyurea synthesis methods are difficult to industrialize and have poor product quality. When they continue to be applied to downstream products, the physical and chemical properties they exhibit are also unsatisfactory.
[0078] The non-isocyanate polyurea process according to the present invention is simple and has a high reaction rate. When it is used as a raw material to prepare water-based non-isocyanate polyurea, the coating has excellent mechanical properties (including tensile strength, elongation at break, and tear strength); and when the non-isocyanate polyurea is used as a film-forming substance to prepare an anti-corrosion coating, the resulting coating has excellent corrosion resistance, high physical properties, and a long service life; and when the non-isocyanate polyurea is used as a film-forming substance to prepare a waterproof coating, the resulting coating has good elongation at break, tensile strength, and tear strength; and when the water-based non-isocyanate polyurea prepared from the non-isocyanate polyurea is used as a film-forming substance to prepare an intumescent steel structure fire retardant coating and a transparent finishing type fire retardant coating, the resulting coating has excellent fire resistance, good water resistance, and excellent bonding strength.
[0079] In the present application, unless otherwise specified, the term "ionic liquid" has the conventional meaning of the term in the art. Specifically, an ionic liquid is a salt composed of an organic cation and an inorganic or organic anion that is liquid at or near room temperature.
[0080] Specifically, according to a first aspect of the present invention, a method for preparing a non-isocyanate polyurea is provided, the method comprising the following steps:
[0081] (1) mixing an alkali metal alkoxide and an ionic liquid to obtain an alkali metal alkoxide / ionic liquid composite catalyst; and
[0082] (2) In the presence of the alkali metal alkoxide / ionic liquid composite catalyst, a polyetheramine is mixed with an organic solvent, and then carbon dioxide is introduced to react to obtain the non-isocyanate polyurea, wherein the polyetheramine is an amino-terminated polyoxypropylene diamine or an amino-terminated polyoxypropylene triamine having a number average molecular weight in the range of 230 to 5000.
[0083] Preferably, the alkali metal alkoxide is selected from one or more of sodium methoxide, sodium tert-butoxide, lithium tert-butoxide, potassium tert-butoxide and sodium ethoxide.
[0084] Preferably, the ionic liquid is an imidazolium acetate ionic liquid, a pyridine acetate ionic liquid or a combination thereof.
[0085] Preferably, the ionic liquid is selected from one or more of 1,3-dimethylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-propyl-3-methylimidazolium acetate, 1-pentyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-hexyl-3-methylimidazolium acetate, 1-heptyl-3-methylimidazolium acetate, 1-octyl-3-methylimidazolium acetate, 1-decyl-3-methylimidazolium acetate, 1-ethyl-2,3-dimethylimidazolium acetate, 1-butyl-2,3-dimethylimidazolium acetate, N-ethylpyridine acetate and N-butylpyridine acetate.
[0086] The inventors of the present invention have found in their research that by using an alkali metal alkoxide / ionic liquid complex prepared from a specific alkali metal alkoxide and a specific ionic liquid as a catalyst for the reaction of polyetheramine with carbon dioxide, non-isocyanate polyurea can be prepared with a high reaction rate through a simple process route.
[0087] Preferably, the organic solvent is one or more of xylene, acetone, ethyl acetate and ethylene glycol dimethyl ether.
[0088] The inventors have found in the research that in the above technical scheme using amino-terminated polyoxypropylene diamine as polyetheramine, the number average molecular weight of the amino-terminated polyoxypropylene diamine used has an important influence on the physical properties of the obtained product non-isocyanate polyurea. By controlling the number average molecular weight of the amino-terminated polyoxypropylene diamine within the range of 230 to 4000, and the number average molecular weight of the product non-isocyanate polyurea within the range of 50,000-600,000, the physical properties of the non-isocyanate polyurea (including elongation at break, tensile strength and tear strength, etc.) are good. In particular, when the number average molecular weight of the amino-terminated polyoxypropylene diamine is further controlled within the range of 400 to 2000, and the number average molecular weight of the product non-isocyanate polyurea is controlled within the range of 200,000-350,000, the physical properties of the non-isocyanate polyurea (including elongation at break, tensile strength and tear strength, etc.) can reach the performance standard determined as "excellent" in the industry.
[0089] In addition, in the above technical solution using amino-terminated polyoxypropylene triamine as polyetheramine, the number average molecular weight of the amino-terminated polyoxypropylene triamine used has an important influence on the physical properties of the obtained non-isocyanate polyurea. By controlling the number average molecular weight of the amino-terminated polyoxypropylene triamine within the range of 440 to 5000, and the number average molecular weight of the product non-isocyanate polyurea within the range of 50,000-600,000, the physical properties of the non-isocyanate polyurea (including elongation at break, tensile strength and tear strength, etc.) are good. In particular, when the number average molecular weight of the amino-terminated polyoxypropylene triamine is further controlled within the range of 440 to 3000, and the number average molecular weight of the product non-isocyanate polyurea is controlled within the range of 200,000-350,000, the physical properties of the non-isocyanate polyurea (including elongation at break, tensile strength and tear strength, etc.) can reach the performance standards determined as "excellent" in the industry.
[0090] Preferably, the amino-terminated polyoxypropylenediamine has a structure represented by the following general formula (1):
[0091]
[0092] Where n is the degree of polymerization.
[0093] Specific examples of amino-terminated polyoxypropylene diamines that can be used in the present invention include: JEFFAMINE series products D230, D400, D2000, and D4000 produced and sold by Huntsman Company in the United States.
[0094] Preferably, the amino-terminated polyoxypropylene triamine has a structure represented by the following general formula (2):
[0095]
[0096] Where a, b and c are the degrees of polymerization.
[0097] Specific examples of amino-terminated polyoxypropylene triamines that can be used in the present invention include: JEFFAMINE series products T403, T3000, and T5000 produced and sold by Huntsman Company in the United States.
[0098] The alkali metal alkoxide / ionic liquid composite catalyst prepared in the present invention can make the diamine molecule have higher reactivity and improve the capture rate of carbon dioxide. Preferably, in step (1), the weight ratio of the alkali metal alkoxide to the ionic liquid is in the range of 1:5 to 1:20, the reaction temperature is 50-70°C, and the reaction time is 3-5h. Preferably, the organic base is selected from one or more of sodium methoxide, sodium tert-butoxide, lithium tert-butoxide, potassium tert-butoxide and sodium ethoxide. Preferably, the ionic liquid is selected from one or more of 1,3-dimethylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-propyl-3-methylimidazolium acetate, 1-pentyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-hexyl-3-methylimidazolium acetate, 1-heptyl-3-methylimidazolium acetate, 1-octyl-3-methylimidazolium acetate, 1-decyl-3-methylimidazolium acetate, 1-ethyl-2,3-dimethylimidazolium acetate, 1-butyl-2,3-dimethylimidazolium acetate, N-ethylpyridine acetate, and N-butylpyridine acetate.
[0099] Preferably, in step (2), the ratio of the weight of the alkali metal alkoxide / ionic liquid composite catalyst to the weight of the polyetheramine is 1×10 -5 : 1 to 1×10 -3 : 1, preferably 1×10 -4 : 1 to 5×10 -4 : Within the range of 1.
[0100] Preferably, in step (2), the reaction temperature is 150-190° C., the reaction pressure is 10.6-23.5 MPa, and the reaction time is 6-11 h.
[0101] Optionally, an organic solvent is added to the reaction system to adjust the viscosity of the reaction system and the product non-isocyanate polyurea. Preferably, the solvent is one or more of xylene, acetone, ethyl acetate, and ethylene glycol dimethyl ether.
[0102] Preferably, the weight ratio of the polyetheramine to the added organic solvent is in the range of 3:1 to 1:1.
[0103] According to a second aspect of the present invention, a non-isocyanate polyurea is provided, and the non-isocyanate polyurea is prepared according to the method described above. Preferably, the non-isocyanate polyurea is an amine-terminated linear polymer. The non-isocyanate polyurea as an amine-terminated linear polymer is more excellent in tensile strength, elongation at break, and tear strength. Preferably, the non-isocyanate polyurea is an amine-terminated branched polymer. The non-isocyanate polyurea as an amine-terminated branched polymer is more excellent in aging resistance, chemical corrosion resistance, etc.
[0104] According to a third aspect of the present invention, there is provided a method for preparing a water-based non-isocyanate polyurea, the method comprising the following steps:
[0105] (1) preparing a non-isocyanate polyurea according to the preparation method described above;
[0106] (2) Under dispersion conditions, an emulsifier is added to the non-isocyanate polyurea prepared in step (1), followed by slow addition of water, and then the solvent is removed by distillation under reduced pressure to obtain an aqueous non-isocyanate polyurea.
[0107] According to certain preferred embodiments of the present invention, in step (2), the emulsifier is a polyoxyethylene ether emulsifier, preferably a fatty alcohol polyoxyethylene ether, such as ME5110 and ME5120 from Lianhong New Materials and E-1309 from Shanghai Xiangu Chemical.
[0108] Preferably, in step (2), the amount of the emulsifier added is 2%-10% by weight of the non-isocyanate polyurea.
[0109] Preferably, in step (2), the weight ratio of the non-isocyanate polyurea to the added water is in the range of 1:1 to 1:5.
[0110] According to the fourth aspect of the present invention, a non-isocyanate polyurea anti-corrosion coating is provided, which comprises: 50-80 parts by weight of the non-isocyanate polyurea prepared according to the preparation method described above, 10-30 parts by weight of titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoaming agent, 0.3-1.0 parts by weight of an ultraviolet absorber and 2-20 parts by weight of a solvent.
[0111] Preferably, the titanium dioxide is rutile titanium dioxide; the defoamer is a polyolefin solution defoamer, for example, one of BYK-1790 and BYK-1799; the dispersant is a polyphosphate wetting dispersant DISPERBYK-110; the ultraviolet absorber is a benzotriazole ultraviolet absorber, for example, ultraviolet absorber UV-326; the solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate and xylene.
[0112] According to a fifth aspect of the present invention, a non-isocyanate polyurea waterproof coating is provided, comprising: 25-43 parts by weight of the non-isocyanate polyurea prepared according to the preparation method described above, 20-28 parts by weight of a plasticizer, 25-36 parts by weight of a filler, 0.1-0.5 parts by weight of a defoamer and 3-11 parts by weight of a solvent.
[0113] Preferably, the plasticizer is one or more of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, trioctyl phosphate, citrate, and chlorinated paraffin plasticizers; the pigment filler is one or more of rutile titanium dioxide, kaolin, heavy calcium carbonate, barium sulfate, magnesium oxide, calcium oxide, wollastonite, and talc; the defoamer is a polyolefin solution defoamer, for example, one of BYK-1790 and BYK-1799; the solvent is one or more of xylene, solvent oil, ethyl acetate, butyl acetate, and propylene glycol methyl ether acetate.
[0114] According to a sixth aspect of the present invention, a water-based non-isocyanate polyurea-based intumescent fire-retardant coating for steel structures is provided, wherein the water-based polyurea-based intumescent fire-retardant coating for steel structures comprises: 25-35 parts by weight of a water-based non-isocyanate polyurea prepared according to the preparation method described above, 0.1-1 parts by weight of a defoamer, 0.5-1 parts by weight of a dispersant, 0.1-0.5 parts by weight of a pH regulator, 5-20 parts by weight of titanium dioxide, 6-15 parts by weight of melamine, 6-15 parts by weight of pentaerythritol, 20-30 parts by weight of ammonium polyphosphate, 0.3-1 parts by weight of a thickener and 10-25 parts by weight of water.
[0115] Preferably, the defoamer is a composite silicone defoamer, for example, one of SN-DEFOAMER327 and SN-DEFOAMER328 provided by San Nopco Co., Ltd. of Japan; the dispersant is an aqueous solution of modified styrene maleic anhydride copolymer, for example, one of BYK-2010 and DISPERBYK-2012 provided by BYK of Germany; the pH adjuster is an aqueous solution of reactive silicone, for example, one of SN-DEFOAMER327 and SN-DEFOAMER328 provided by Wacker of Germany; BS168; the titanium dioxide is rutile titanium dioxide, for example, R930 provided by Ishihara Co., Ltd. of Japan and R996 provided by Sichuan Longmang Titanium Industry Co., Ltd.; the ammonium polyphosphate is type II ammonium polyphosphate with a degree of polymerization n>1000 and a water solubility of ≤0.5 g / 100 ml, for example, ExolitAP422 and ExolitAP428 provided by Clariant of Germany and JLS-APP provided by Hangzhou Jieersi Flame Retardant Chemical Co., Ltd.; the thickener is a polyurethane modified polyether associative thickener, for example, provided by Wanhua Chemical Group Co., Ltd. One of U505 and BYK-425 provided by BYK of Germany.
[0116] According to the seventh aspect of the present invention, a water-based non-isocyanate polyurea-based transparent finishing fire-retardant coating is provided, and the water-based non-isocyanate polyurea-based transparent finishing fire-retardant coating comprises: 25-35 parts by weight of water-based non-isocyanate polyurea prepared according to the preparation method described above, 0.1-1 parts by weight of a defoamer, 0.1-0.3 parts by weight of a pH adjuster, 8-15 parts by weight of a polyol, 20-30 parts by weight of ammonium polyphosphate, 8-15 parts by weight of an aqueous amino resin, 0.5-1 parts by weight of a thickener and 10-25 parts by weight of water.
[0117] Preferably, the defoamer is a composite silicone defoamer, such as SN-DEFOAMER327 and SN-DEFOAMER328 provided by Japan San Nopco Co., Ltd.; the pH adjuster is an aqueous solution of reactive organic silicon, such as SN-DEFOAMER327 provided by Germany Wacker Co., Ltd. BS168; the polyol is selected from one or more of sorbitol, xylitol and maltitol; the ammonium polyphosphate is a short-chain low-polymerization ammonium polyphosphate with a polymerization degree n≤20 and completely soluble in water, for example, the ammonium polyphosphate with a polymerization degree of 15 produced by Guangzhou Haoyu Co., Ltd.; the water-based amino resin is a methyl etherified melamine amino resin, for example, CYMEL385 provided by Zhanxin Group and S5325 provided by Changzhou Sisai New Materials Technology Co., Ltd.; the thickener is a polyurethane modified polyether associative thickener, for example, the thickener provided by Wanhua Chemical Group Co., Ltd. One of U505 and BYK-425 provided by BYK of Germany.
[0118] The present invention is described in more detail below in conjunction with the examples. It should be noted that these descriptions and examples are intended to facilitate the understanding of the present invention, rather than to limit the present invention. The protection scope of the present invention shall be subject to the attached claims.
[0119] Example
[0120] In the present invention, unless otherwise specified, the reagents used are commercial products and are used directly without further purification. In addition, the "%" mentioned is "% by weight", and the "parts" mentioned are "parts by weight".
[0121] Test Method
[0122] Tensile strength, elongation at break and tear strength test of non-isocyanate polyurea coating after curing
[0123] The tensile strength, elongation at break and tear strength of the non-isocyanate polyurea coating obtained in each embodiment and comparative example after curing were measured. For specific measurement methods, refer to the relevant test methods in GB / T16777-2008 "Test Methods for Building Waterproof Coatings". Among them, if the tensile strength of the coating is greater than or equal to 6.0MPa, it is considered to meet the general industrial application requirements of non-isocyanate polyurea elastomers; if the tensile strength of the coating is greater than or equal to 12MPa, the tensile strength performance of the non-isocyanate polyurea elastomer is considered to be excellent. If the elongation at break is greater than or equal to 250%, it is considered to meet the general industrial application requirements of non-isocyanate polyurea elastomers; if the elongation at break is greater than or equal to 450%, the elongation at break performance of the non-isocyanate polyurea elastomer is considered to be excellent. If the tear strength is greater than or equal to 30N / mm, it is considered to meet the general industrial application requirements of non-isocyanate polyurea elastomers; if the tear strength is greater than or equal to 40N / mm, the tear strength performance of the non-isocyanate polyurea elastomer is considered to be excellent.
[0124] Tensile strength, elongation at break and tear strength test of water-based non-isocyanate polyurea coating after curing
[0125] The tensile strength, elongation at break and tear strength of the water-based non-isocyanate polyurea coating obtained in each embodiment and comparative example after curing are measured. For specific measurement methods, refer to the relevant test methods in GB / T16777-2008 "Test Methods for Building Waterproof Coatings". Among them, if the tensile strength of the coating is greater than or equal to 6.0MPa, it is considered to meet the general industrial application requirements of water-based non-isocyanate polyurea materials; if the tensile strength of the coating is greater than or equal to 12MPa, it is considered that the tensile strength performance of the water-based non-isocyanate polyurea material is excellent. If the elongation at break is greater than or equal to 250%, it is considered to meet the general industrial application requirements of water-based non-isocyanate polyurea materials; if the elongation at break is greater than or equal to 450%, it is considered that the elongation at break of the water-based non-isocyanate polyurea material is excellent. If the tear strength is greater than or equal to 30 N / mm, it is considered to meet the general industrial application requirements of water-based non-isocyanate polyurea materials; if the tear strength is greater than or equal to 40 N / mm, the tear strength performance of the water-based non-isocyanate polyurea material is considered to be excellent.
[0126] Solid content test of water-based non-isocyanate polyurea
[0127] The solid content of the water-based non-isocyanate polyurea obtained in the following examples and comparative examples was determined according to the test method in the national standard GB / T20623-2006 “Emulsions for architectural coatings”.
[0128] Specifically, bake a flat-bottomed disc (about 75 mm in diameter) in a forced air oven at (150±2)°C for 15 minutes, cool it to room temperature in a desiccator, and weigh (m0) to an accuracy of 1 mg. Weigh about 1 g of the test product (m1) into the disc with the same accuracy, and ensure that the sample is evenly dispersed on the surface of the disc. If the viscosity of the sample is too high, dilute the weighed sample with water and stir it evenly. Place the weighed disc into a forced air oven preheated to (150±2)°C and keep it for 15 minutes. Move the disc into a desiccator, cool it to room temperature, and then weigh (m 2) ), accurate to 1 mg.
[0129] The solid content is calculated according to equation (1):
[0130]
[0131] Where:
[0132] W NV ——Solid content of water-based non-isocyanate polyurea (%);
[0133] m2——The mass of the sample and the disc after heating, in g;
[0134] m0——mass of the disk, in g;
[0135] m1 – the mass of the sample before heating, in g.
[0136] The test results are expressed as the average value of the two tests, accurate to one decimal place.
[0137] Mechanical stability test of water-based non-isocyanate polyurea
[0138] The mechanical stability of the water-based non-isocyanate polyurea obtained in the following examples and comparative examples was determined according to the test method in the national standard GB / T20623-2006.
[0139] Specifically, weigh (400±0.52) g of the filtered emulsion [filter with a pore size of 17 μm (80 mesh)] in a container of about 1000 mL (100 mm in diameter and 180 mm in height), place it on a high-speed disperser stand, fix it with a clip, start the disperser (the stirring head is a disc-shaped toothed head with a diameter of about 40 mm), adjust the speed to 2500 r / min, disperse for 0.5 h, filter again, and flush the residue on the inner wall of the container into the filter with tap water, rinse the filter with tap water, and observe whether the emulsion is demulsified and whether there are obvious flocculants. If the above situation does not exist, it is considered to be mechanically stable.
[0140] Calcium Ion Stability Test of Waterborne Non-isocyanate Polyurea
[0141] The calcium ion stability of the water-based non-isocyanate polyurea obtained in the following examples and comparative examples was determined according to the test method in the national standard GB / T20623-2006.
[0142] Specifically, add 30 mL of the emulsion to a beaker, then add 6 mL of a 0.5% CaCl2 solution, stir well, and place in a 50 mL stoppered measuring cylinder. After 48 hours, observe whether there are stratification, precipitation, flocculation, etc. The sample can be spread on a glass plate into a uniform thin layer with the help of a glass rod, and then observe whether there are flocculations. If the above conditions do not exist, it is considered to be calcium ion stable.
[0143] Physical property test and acid and alkali resistance test of non-isocyanate polyurea anticorrosive coating
[0144] The physical properties and anticorrosion performance of the non-isocyanate polyurea anticorrosive coatings obtained in each embodiment and comparative example are measured. For specific measurement methods, please refer to the relevant test methods in JG / T224-2007 "Anticorrosion Coatings for Steel Structures in Construction". Among them, if the acid resistance is greater than or equal to 96h, it is considered to meet the general industrial application requirements of anticorrosion coating materials for steel structures in construction; if the acid resistance is greater than or equal to 168h, it is considered that the anticorrosion coating for steel structures in construction has excellent acid resistance. If the salt water resistance is greater than or equal to 120h, it is considered to meet the general industrial application requirements of anticorrosion coating materials for steel structures in construction; if the salt water resistance is greater than or equal to 240h, it is considered that the anticorrosion coating for steel structures in construction has excellent salt water resistance. If the salt spray resistance is greater than or equal to 500h, it is considered to meet the general industrial application requirements of anticorrosion coating materials for steel structures in construction; if the salt spray resistance is greater than or equal to 1000h, it is considered that the anticorrosion coating for steel structures in construction has excellent salt spray resistance. If the artificial aging resistance is greater than or equal to 500h, it is considered to meet the general industrial application requirements of anti-corrosion coating materials for steel structures for construction; if the artificial aging resistance is greater than or equal to 1000h, it is considered that the anti-corrosion coating for steel structures for construction has excellent artificial aging resistance.
[0145] Tensile strength, elongation at break and tear strength test of non-isocyanate polyurea waterproof coating film after curing
[0146] The tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film obtained in each embodiment and comparative example after curing were measured. For specific measurement methods, refer to the relevant test methods in GB / T19250-2013 "Polyurethane Waterproof Coating". Among them, if the tensile strength of the coating film is greater than or equal to 6.0MPa, it is considered to meet the general industrial application requirements of polyurethane waterproof coating materials for construction; if the tensile strength of the coating film is greater than or equal to 12MPa, the tensile strength performance of the polyurethane waterproof coating material for construction is considered to be excellent. If the elongation at break is greater than or equal to 250%, it is considered to meet the general industrial application requirements of polyurethane waterproof coating materials for construction; if the elongation at break is greater than or equal to 450%, the elongation at break performance of the polyurethane waterproof coating material for construction is considered to be excellent. If the tear strength is greater than or equal to 30N / mm, it is considered to meet the general industrial application requirements of polyurethane waterproof coating materials for construction; if the tear strength is greater than or equal to 40N / mm, the tear strength performance of the polyurethane waterproof coating material for construction is considered to be excellent.
[0147] Physical property test and fire performance test of water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating
[0148] The physical properties and fire retardant properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coatings obtained in each embodiment and comparative example were measured. For specific measurement methods, refer to the relevant test methods in GB / T14907-2018 "Steel Structure Fire Retardant Coatings". Among them, if the bonding strength is greater than or equal to 0.15MPa, it is considered to meet the general industrial application requirements of intumescent steel structure fire retardant coating materials for construction; if the bonding strength is greater than or equal to 0.3MPa, it is considered that the intumescent steel structure fire retardant coating for construction has excellent bonding strength performance. If the water resistance is greater than or equal to 24h, it is considered to meet the general industrial application requirements of intumescent steel structure fire retardant coating materials for construction; if the water resistance is greater than or equal to 48h, it is considered that the intumescent steel structure fire retardant coating for construction has excellent water resistance. If the fire resistance is greater than or equal to 0.5h, it is considered to meet the general industrial application requirements of intumescent steel structure fire retardant coating materials for construction; if the fire resistance is greater than or equal to 1.0h, it is considered that the intumescent steel structure fire retardant coating for construction has excellent fire resistance.
[0149] Physical property test and fire performance test of water-based non-isocyanate polyurea-based transparent finishing fire retardant coating
[0150] The physical properties and fire retardant properties of the water-based non-isocyanate polyurea-based transparent finishing fire retardant coatings obtained in each embodiment and comparative example were measured. For specific measurement methods, please refer to the relevant test methods in GB12441-2018 "Finishing Fire Retardant Coatings". Among them, if the adhesion grade is level 3, it is considered to meet the general industrial application requirements of building finishing fire retardant coating materials; if the adhesion grade is level 2, it is considered that the building finishing fire retardant coating material has excellent adhesion performance. If the water resistance is greater than or equal to 24h, it is considered to meet the general industrial application requirements of building finishing fire retardant coating materials; if the water resistance is greater than or equal to 48h, it is considered that the building finishing fire retardant coating material has excellent water resistance. If the flame retardant time is greater than or equal to 15mmin, it is considered to meet the general industrial application requirements of building finishing fire retardant coating materials; if the flame retardant time is greater than or equal to 20min, it is considered that the building finishing fire retardant coating material has excellent flame retardant performance.
[0151] Example 1
[0152] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of sodium methoxide (Shanghai Aladdin Company) and 8 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Olike New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0153] 100g (0.05mol) of polyetheramine D-2000 and 50g of ethylene glycol dimethyl ether were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.04g of sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the oxygen was replaced three times with carbon dioxide, and heated to 180°C. Then carbon dioxide was introduced into the reactor to keep the pressure in the reactor at 14MPa, and the reaction was carried out for 8h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 265,000 according to analytical chemical testing.
[0154] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 6.5g of emulsifier ME5110 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 50℃ under -0.095MPa pressure, and remove ethylene glycol dimethyl ether by reduced pressure distillation to obtain water-based non-isocyanate polyurea.
[0155] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0156] 70.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.0 parts by weight of DISPERBYK-110, 0.5 parts by weight of BYK-1799, and 14.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 1 part by weight of ultraviolet absorber UV-326 and 13.5 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0157] 42.0 parts by weight of the above-mentioned non-isocyanate polyurea, 22.0 parts by weight of dioctyl phthalate, 0.2 parts by weight of BYK-1799, and 25.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 10.8 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0158] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0159] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 11 parts by weight of deionized water, 0.8 parts by weight of defoamer SN-DEFOAMER327, 0.8 parts by weight of dispersant BYK-2010, 0.4 parts by weight of pH value adjuster BS168, 8 parts by weight of rutile titanium dioxide R930, 13 parts by weight of melamine, 15 parts by weight of pentaerythritol, 25 parts by weight of ammonium polyphosphate ExolitAP422, and 1 part by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0160] 35 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 14 parts by weight of deionized water, 0.2 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of pH value adjuster BS168, 15 parts by weight of aqueous amino resin CYMEL385, 15 parts by weight of maltose powder, 20 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.6 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0161] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0162] Example 2
[0163] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of sodium methoxide (Shanghai Aladdin Company) and 8 grams of 1Δ ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Olike New Materials Company) were added, nitrogen was introduced, and the mixture was mixed evenly at room temperature to obtain a sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0164] 150g (0.05mol) of polyetheramine T-3000 and 75g of ethylene glycol dimethyl ether were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.075g of sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the mixture was replaced three times with carbon dioxide to remove oxygen, and heated to 180°C. Carbon dioxide was then introduced into the reactor to maintain the pressure in the reactor at 12MPa, and the reaction was performed for 7h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 283,000 as determined by analytical chemistry testing.
[0165] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 7.0g of emulsifier ME5110 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 50℃ under -0.095MPa pressure, and remove ethylene glycol dimethyl ether by reduced pressure distillation to obtain water-based non-isocyanate polyurea.
[0166] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0167] 63.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.5 parts by weight of DISPERBYK-110, 0.8 parts by weight of BYK-1799, and 18.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 0.5 parts by weight of ultraviolet absorber UV-326 and 16.2 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0168] 39.0 parts by weight of the above-mentioned non-isocyanate polyurea, 20.0 parts by weight of dioctyl phthalate, 0.3 parts by weight of BYK-1790, and 27.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 13.7 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0169] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0170] 26 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 10 parts by weight of deionized water, 0.5 parts by weight of defoamer SN-DEFOAMER327, 0.5 parts by weight of dispersant BYK-2012, 0.5 parts by weight of pH adjuster BS168, 6 parts by weight of rutile titanium dioxide R930, 15 parts by weight of melamine, 13 parts by weight of pentaerythritol, 28 parts by weight of ammonium polyphosphate ExolitAP422, and 0.5 parts by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0171] 32.7 parts by weight of the above-mentioned aqueous non-isocyanate polyurea, 25 parts by weight of deionized water, 1 part by weight of defoamer SN-DEFOAMER327, 0.3 parts by weight of pH adjuster BS168, 9 parts by weight of water-based amino resin CYMEL385, 9 parts by weight of maltose powder, 22 parts by weight of ammonium polyphosphate (degree of polymerization is 15), and 1 part by weight of thickener BYK-425 are dispersed at a speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0172] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0173] Example 3
[0174] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of lithium tert-butoxide (Shanghai Aladdin Company) and 10 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Oriko New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a lithium tert-butoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0175] 107.5g (0.25mol) polyetheramine D-400 and 53.75g ethyl acetate were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.054g lithium tert-butyl alcohol / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the mixture was replaced three times with carbon dioxide to remove oxygen, and heated to 170°C. Carbon dioxide was then introduced into the reactor to maintain the pressure in the reactor at 16MPa, and the reaction was performed for 9h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 273,000 as determined by analytical chemistry testing.
[0176] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 5.0g of emulsifier ME5120 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 45°C under -0.095MPa pressure, and remove ethyl acetate by reduced pressure distillation to obtain water-based non-isocyanate polyurea.
[0177] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0178] 80.0 parts by weight of the above-mentioned non-isocyanate polyurea, 0.5 parts by weight of DISPERBYK-110, 0.5 parts by weight of BYK-1799, and 12.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 1 part by weight of ultraviolet absorber UV-326 and 6.0 parts by weight of butyl acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0179] 30.0 parts by weight of the above-mentioned non-isocyanate polyurea, 28.0 parts by weight of trioctyl phosphate, 0.2 parts by weight of BYK-1799, and 29.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 12.8 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0180] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0181] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 11 parts by weight of deionized water, 0.8 parts by weight of defoamer SN-DEFOAMER327, 0.8 parts by weight of dispersant BYK-2010, 0.4 parts by weight of pH value adjuster BS168, 8 parts by weight of rutile titanium dioxide R930, 13 parts by weight of melamine, 15 parts by weight of pentaerythritol, 25 parts by weight of ammonium polyphosphate ExolitAP422, and 1 part by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0182] 35 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 14 parts by weight of deionized water, 0.2 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of pH value adjuster BS1 68, 15 parts by weight of aqueous amino resin CYMEL385, 15 parts by weight of maltose powder, 20 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.6 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0183] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0184] Example 4
[0185] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of lithium tert-butoxide (Shanghai Aladdin Company) and 10 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Oriko New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a lithium tert-butoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0186] 110g (0.25mol) of polyetheramine T-403 and 55g of ethyl acetate were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.033g of lithium tert-butyl alcohol / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the oxygen was replaced three times with carbon dioxide, and heated to 170°C. Then carbon dioxide was introduced into the reactor to keep the pressure in the reactor at 13MPa, and the reaction was carried out for 8h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 281,000 according to analytical chemical testing.
[0187] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 6.0g of emulsifier ME5110 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 45°C under -0.095MPa pressure, and remove ethyl acetate by vacuum distillation to obtain water-based non-isocyanate polyurea.
[0188] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0189] 55.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.5 parts by weight of DISPERBYK-110, 0.8 parts by weight of BYK-1799, and 28.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 0.7 parts by weight of ultraviolet absorber UV-326 and 14.0 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0190] 42.0 parts by weight of the above-mentioned non-isocyanate polyurea, 22.0 parts by weight of dioctyl phthalate, 0.4 parts by weight of BYK-1799, and 25.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 min; then 10.6 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 min to obtain a non-isocyanate polyurea waterproof coating.
[0191] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0192] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 11 parts by weight of deionized water, 0.8 parts by weight of defoamer SN-DEFOAMER327, 0.8 parts by weight of dispersant BYK-2010, 0.4 parts by weight of pH value adjuster BS168, 8 parts by weight of rutile titanium dioxide R930, 13 parts by weight of melamine, 15 parts by weight of pentaerythritol, 25 parts by weight of ammonium polyphosphate ExolitAP422, and 1 part by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0193] 35 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 14 parts by weight of deionized water, 0.2 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of pH value adjuster BS168, 15 parts by weight of aqueous amino resin CYMEL385, 15 parts by weight of maltose powder, 20 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.6 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0194] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0195] Example 5
[0196] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of sodium methoxide (Shanghai Aladdin Company) and 8 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Olike New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0197] 100g (0.05mol) of polyetheramine D-2000 and 50g of ethylene glycol dimethyl ether were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.04g of sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the oxygen was replaced three times with carbon dioxide, and heated to 180°C. Then carbon dioxide was introduced into the reactor to keep the pressure in the reactor at 18MPa, and the reaction was carried out for 9h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 273,000 according to analytical chemical testing.
[0198] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 8g of emulsifier ME5120 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 50℃ under -0.095MPa pressure, and remove ethylene glycol dimethyl ether by vacuum distillation to obtain water-based non-isocyanate polyurea.
[0199] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0200] 75.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.0 parts by weight of DISPERBYK-110, 0.5 parts by weight of BYK-1790, and 16.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 1 part by weight of ultraviolet absorber UV-326 and 6.5 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0201] 40.0 parts by weight of the above-mentioned non-isocyanate polyurea, 20.0 parts by weight of trioctyl phosphate, 0.3 parts by weight of BYK-1799, and 28.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 11.7 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0202] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0203] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 22 parts by weight of deionized water, 1 part by weight of defoamer SN-DEFOAMER327, 0.6 parts by weight of dispersant BYK-2010, 0.4 parts by weight of pH value adjuster BS1 68, 5 parts by weight of rutile titanium dioxide R930, 8 parts by weight of melamine, 7 parts by weight of pentaerythritol, 30 parts by weight of ammonium polyphosphate ExolitAP422, and 0.1 parts by weight of thickener BYK-425 are dispersed at a speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0204] 35 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 17 parts by weight of deionized water, 1 part by weight of defoamer SN-DEFOAMER328, 0.2 parts by weight of pH adjuster BS168, 8 parts by weight of water-based amino resin S5325, 8 parts by weight of sorbitol powder, 30 parts by weight of ammonium polyphosphate (degree of polymerization is 15), and 0.8 parts by weight of thickener BYK-425 are dispersed at a speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0205] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0206] Example 6
[0207] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of lithium tert-butoxide (Shanghai Aladdin Company) and 10 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Oriko New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a lithium tert-butoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0208] 110g (0.25mol) of polyetheramine T-403 and 55g of ethyl acetate were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.055g of lithium tert-butyl alcohol / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the oxygen was replaced three times with carbon dioxide, and heated to 190°C. Then carbon dioxide was introduced into the reactor to keep the pressure in the reactor at 20MPa, and the reaction was carried out for 10h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 302,000 as determined by analytical chemical testing.
[0209] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 9g of emulsifier ME5110 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 45°C under -0.095MPa pressure, and remove ethyl acetate by vacuum distillation to obtain water-based non-isocyanate polyurea.
[0210] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0211] 65.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.5 parts by weight of DISPERBYK-110, 0.6 parts by weight of BYK-1799, and 21.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 1.0 parts by weight of ultraviolet absorber UV-326 and 10.9 parts by weight of xylene are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0212] 32.0 parts by weight of the above-mentioned non-isocyanate polyurea, 24.0 parts by weight of dioctyl phthalate, 0.1 parts by weight of BYK-1799, and 31.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 12.9 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0213] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0214] 30 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 19 parts by weight of deionized water, 0.4 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of dispersant BYK-2010, 0.5 parts by weight of pH value adjuster BS168, 20 parts by weight of rutile titanium dioxide R996, 6 parts by weight of melamine, 6 parts by weight of pentaerythritol, 20 parts by weight of ammonium polyphosphate JLS-APP, and 0.4 parts by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0215] 29 parts by weight of the above-mentioned aqueous non-isocyanate polyurea, 10 parts by weight of deionized water, 0.1 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of pH value adjuster BS168, 15 parts by weight of water-based amino resin CYMEL385, 15 parts by weight of xylitol powder, 30 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.7 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0216] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0217] Example 7
[0218] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of lithium tert-butoxide (Shanghai Aladdin Company) and 10 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Oriko New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a lithium tert-butoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0219] 115g (0.5mol) of polyetheramine D-230 and 57.5g of ethylene glycol dimethyl ether were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.058g of lithium tert-butyl alcohol / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the mixture was replaced three times with carbon dioxide to remove oxygen, and heated to 180°C. Carbon dioxide was then introduced into the reactor to maintain the pressure in the reactor at 17MPa, and the reaction was performed for 9h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 263,000 as determined by analytical chemistry testing.
[0220] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 7.5g of emulsifier ME5120 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 50℃ under -0.095MPa pressure, and remove ethylene glycol dimethyl ether by reduced pressure distillation to obtain water-based non-isocyanate polyurea.
[0221] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0222] 60.0 parts by weight of the above-mentioned non-isocyanate polyurea, 1.0 parts by weight of DISPERBYK-110, 0.5 parts by weight of BYK-1790, and 28.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / min for 30 minutes; then 0.8 parts by weight of ultraviolet absorber UV-326 and 9.7 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0223] 26.0 parts by weight of the above-mentioned non-isocyanate polyurea, 28.0 parts by weight of trioctyl phosphate, 0.5 parts by weight of BYK-1799, and 36.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 minutes; then 9.5 parts by weight of propylene glycol methyl ether acetate were added and dispersed at 600 r / min for 15 minutes to obtain a non-isocyanate polyurea waterproof coating.
[0224] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0225] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 25 parts by weight of deionized water, 0.5 parts by weight of defoamer SN-DEFOAMER327, 1 part by weight of dispersant BYK-2010, 0.2 parts by weight of pH value adjuster BS168, 15 parts by weight of rutile titanium dioxide R996, 7 parts by weight of melamine, 6 parts by weight of pentaerythritol, 20 parts by weight of ammonium polyphosphate ExolitAP422, 0.3 parts by weight of thickener U505 is dispersed at a speed of 500r / min for 1.0h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0226] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 16 parts by weight of deionized water, 0.25 parts by weight of defoamer SN-DEFOAMER327, 0.25 parts by weight of pH value adjuster BS168, 15 parts by weight of water-based amino resin CYMEL385, 13 parts by weight of xylitol powder, 30 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.5 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0227] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0228] Comparative Example 1
[0229] The non-isocyanate polyurea was prepared according to a method similar to that of Example 1, and then a derivative product of the non-isocyanate polyurea was prepared, except that during the preparation of the non-isocyanate polyurea, the reaction pressure was adjusted to 5.0 MPa. The number average molecular weight of the non-isocyanate polyurea was 55,000 as determined by analytical chemical testing.
[0230] The non-isocyanate polyurea is prepared to obtain a derivative product of the non-isocyanate polyurea.
[0231] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0232] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0233] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0234] Comparative Example 2
[0235] The non-isocyanate polyurea and the derivative of the non-isocyanate polyurea were prepared according to a method similar to that of preparing the non-isocyanate polyurea in Example 2, except that in the process of preparing the water-based non-isocyanate polyurea, the amount of emulsifier added was reduced to 1%.
[0236] The non-isocyanate polyurea is prepared to obtain a derivative product of the non-isocyanate polyurea.
[0237] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0238] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0239] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0240] Comparative Example 3
[0241] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 1 gram of sodium methoxide (Shanghai Aladdin Company) and 8 grams of 1-ethyl-3-methylimidazolium acetate ionic liquid (Qingdao Olike New Materials Company) were added, nitrogen was introduced, and mixed evenly at room temperature to obtain a sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst.
[0242] 100g (0.05mol) of polyetheramine D-2000 and 50g of ethylene glycol dimethyl ether were placed in a 500mL stainless steel reactor, the stirring paddle was turned on to stir evenly, 0.04g of sodium methoxide / 1-ethyl-3-methylimidazolium acetate ionic liquid composite catalyst was added, and the oxygen was replaced three times with carbon dioxide, and heated to 180°C. Then carbon dioxide was introduced into the reactor to keep the pressure in the reactor at 14MPa, and the reaction was carried out for 8h to obtain non-isocyanate polyurea. The number average molecular weight of the non-isocyanate polyurea was 265,000 according to analytical chemical testing.
[0243] Take 100g of the non-isocyanate polyurea prepared in the above steps, add 6.5g of emulsifier ME5110 and disperse evenly under the condition of 1500r / min speed of the disperser, then slowly add 200g of water and keep the high speed for 1.5h. Raise the temperature to 50℃ under -0.095MPa pressure, and remove ethylene glycol dimethyl ether by reduced pressure distillation to obtain water-based non-isocyanate polyurea.
[0244] According to the method described in detail above for determining the tensile strength, elongation at break and tear strength of non-isocyanate polyurea coatings, the solid content, mechanical stability and calcium ion stability of water-based non-isocyanate polyurea, and the tensile strength, elongation at break and tear strength of water-based non-isocyanate polyurea coatings, the corresponding properties of the non-isocyanate polyurea and water-based non-isocyanate polyurea prepared above were tested, and the results are shown in the following Table 1.
[0245] 35.0 parts by weight of the above-mentioned non-isocyanate polyurea, 2.0 parts by weight of DISPERBYK-110, 0.1 parts by weight of BYK-1799, and 46.0 parts by weight of titanium dioxide are mixed and dispersed at 1000 r / mmin for 30 minutes; then 0.2 parts by weight of ultraviolet absorber UV-326 and 16.7 parts by weight of propylene glycol methyl ether acetate are added and dispersed at 600 r / mmin for 15 minutes to obtain a non-isocyanate polyurea anticorrosive coating.
[0246] 42.0 parts by weight of the above-mentioned non-isocyanate polyurea, 22.0 parts by weight of dioctyl phthalate, 0.2 parts by weight of BYK-1799, and 25.0 parts by weight of heavy calcium carbonate were mixed and dispersed at 900 r / min for 50 min; then 10.8 parts by weight of butyl acetate were added and dispersed at 600 r / min for 15 min to obtain a non-isocyanate polyurea waterproof coating.
[0247] According to the method described in detail above for determining the substrate adhesion, acid resistance, salt water resistance, salt spray resistance and artificial aging resistance of the non-isocyanate polyurea anti-corrosion coating, the tensile strength, elongation at break and tear strength of the non-isocyanate polyurea waterproof coating film, the corresponding properties of the non-isocyanate polyurea anti-corrosion coating and the non-isocyanate polyurea waterproof coating prepared above were tested, and the results are shown in the following Table 2.
[0248] 25 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 11 parts by weight of deionized water, 0.8 parts by weight of defoamer SN-DEFOAMER327, 0.8 parts by weight of dispersant BYK-2010, 0.4 parts by weight of pH value adjuster BS168, 8 parts by weight of rutile titanium dioxide R930, 13 parts by weight of melamine, 15 parts by weight of pentaerythritol, 25 parts by weight of ammonium polyphosphate ExolitAP422, and 1 part by weight of thickener BYK-425 are dispersed at a rotation speed of 500 r / min for 1.0 h to obtain a water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating.
[0249] 35 parts by weight of the above-mentioned water-based non-isocyanate polyurea, 14 parts by weight of deionized water, 0.2 parts by weight of defoamer SN-DEFOAMER327, 0.2 parts by weight of pH value adjuster BS168, 15 parts by weight of aqueous amino resin CYMEL385, 15 parts by weight of maltose powder, 20 parts by weight of ammonium polyphosphate (degree of polymerization is 15), 0.6 parts by weight of thickener U505 was dispersed at a rotation speed of 500 rpm for 1.0 h to obtain a water-based non-isocyanate polyurea-based transparent finishing fire retardant coating.
[0250] According to the method for determining the performance of fire retardant coatings described in detail above, the corresponding properties of the water-based non-isocyanate polyurea-based intumescent steel structure fire retardant coating and the water-based non-isocyanate polyurea-based transparent finishing fire retardant coating prepared above were tested, and the results are shown in the following Table 3.
[0251]
[0252]
[0253]
[0254] The above Examples 1-7 confirm that the non-isocyanate polyurea prepared according to the method of the present invention has good mechanical properties (such as tensile strength, elongation at break and tear strength) after curing; the water-based non-isocyanate polyurea prepared with the non-isocyanate polyurea as raw material has good emulsion stability (mechanical stability, calcium ion stability); when the non-isocyanate polyurea is used as a raw material to prepare a non-isocyanate polyurea waterproof coating, the coating formed by the non-isocyanate polyurea waterproof coating has good mechanical properties (such as tensile strength, elongation at break and tear strength); when the non-isocyanate polyurea is used as a raw material to prepare a non-isocyanate polyurea anti-corrosion coating, the coating formed by the non-isocyanate polyurea anti-corrosion coating has excellent substrate adhesion and anti-corrosion properties (such as acid resistance, salt water resistance, salt spray resistance and artificial aging resistance); the water-based non-isocyanate polyurea fire retardant coating prepared with the water-based non-isocyanate polyurea has high fire resistance and good physical properties.
[0255] By comparing the results of Example 1 and Comparative Example 1 in Table 1, it can be seen that when the reaction pressure is adjusted to 5.0 MPa during the preparation of non-isocyanate polyurea, the physical properties of the product non-isocyanate polyurea are inferior to those of the product of Example 1, and the performance of its derivative products cannot be guaranteed to be at a good level at the same time.
[0256] By comparing the results of Example 2 and Comparative Example 2 in Table 1, it can be seen that when the amount of emulsifier added is less than 2% (i.e., 1% in Comparative Example 2) during the preparation of water-based non-isocyanate polyurea, the physical properties of the product water-based non-isocyanate polyurea will be inferior to those of the product of Example 2, and many properties of the water-based non-isocyanate polyurea fire retardant coating will be lower than the average level.
[0257] By comparing the results of Example 1 and Comparative Example 3 in Table 2, it can be seen that the weight ratio of the non-isocyanate polyurea resin in the coating has an important influence on the performance of the obtained non-isocyanate polyurea anticorrosive coating. The non-isocyanate polyurea anticorrosive coating prepared by deviating from 50-80 parts by weight of the non-isocyanate polyurea (i.e., as shown in Comparative Example 3, the weight percentage of the non-isocyanate polyurea is 35% by weight) will result in the inability to simultaneously achieve good anticorrosion performance.
[0258] The embodiments described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have all been recorded in the claims.
Claims
1. A method for preparing a non-isocyanate polyurea, the method comprising the following steps: (1) mixing an alkali metal alkoxide and an ionic liquid to obtain an alkali metal alkoxide / ionic liquid composite catalyst; and (2) In the presence of the alkali metal alkoxide / ionic liquid composite catalyst, a polyetheramine is mixed with an organic solvent, and then carbon dioxide is introduced to react to obtain the non-isocyanate polyurea, wherein the polyetheramine is an amino-terminated polyoxypropylene diamine or an amino-terminated polyoxypropylene triamine having a number average molecular weight in the range of 230 to 5000.
2. The method for preparing a non-isocyanate polyurea according to claim 1, wherein the alkali metal alkoxide is selected from one or more of sodium methoxide, sodium tert-butoxide, lithium tert-butoxide, potassium tert-butoxide and sodium ethoxide.
3. The method for preparing non-isocyanate polyurea according to claim 1, wherein the ionic liquid is an imidazole acetate ionic liquid, a pyridine acetate ionic liquid or a combination thereof.
4. The method for preparing a non-isocyanate polyurea according to claim 1, wherein the ionic liquid is selected from one or more of 1,3-dimethylimidazole acetate, 1-ethyl-3-methylimidazole acetate, 1-propyl-3-methylimidazole acetate, 1-pentyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole acetate, 1-hexyl-3-methylimidazole acetate, 1-heptyl-3-methylimidazole acetate, 1Δoctyl-3Δmethylimidazole acetate, 1-decyl-3-methylimidazole acetate, 1-ethyl-2,3-dimethylimidazole acetate, 1-butyl-2,3-dimethylimidazole acetate, N-ethylpyridine acetate and N-butylpyridine acetate.
5. The method for preparing non-isocyanate polyurea according to claim 1, wherein the organic solvent is one or more of xylene, acetone, ethyl acetate and ethylene glycol dimethyl ether.
6. The method for preparing non-isocyanate polyurea according to claim 1, wherein: The number average molecular weight of the amino-terminated polyoxypropylene diamine is between 230 and 4000; and / or The number average molecular weight of the amino-terminated polyoxypropylene triamine is in the range of 440 to 5,000.
7. The method for preparing non-isocyanate polyurea according to claim 1, wherein the number average molecular weight of the non-isocyanate polyurea is in the range of 50,000-600,000, preferably 200,000-350,000.
8. The method for preparing a non-isocyanate polyurea according to claim 1, wherein the amino-terminated polyoxypropylene diamine has a structure represented by the following general formula (1): Where n is the degree of polymerization.
9. The method for preparing a non-isocyanate polyurea according to claim 1, wherein the amino-terminated polyoxypropylene triamine has a structure represented by the following general formula (2): Where a, b and c are the degrees of polymerization.
10. The method for preparing non-isocyanate polyurea according to claim 1, wherein in step (1), under the protection of an inert gas, an alkali metal alkoxide and an ionic liquid are mixed at room temperature to obtain an alkali metal alkoxide / ionic liquid composite catalyst.
11. The method for preparing non-isocyanate polyurea according to claim 1, wherein in step (1), the weight ratio of the alkali metal alkoxide to the ionic liquid is in the range of 1:5 to 1:
20.
12. The method for preparing non-isocyanate polyurea according to claim 1, wherein in step (2), the ratio between the weight of the alkali metal alkoxide / ionic liquid composite catalyst and the weight of the polyetheramine is 1×10 -5 : 1 to 1×10 -3 ∶1 range.
13. The method for preparing non-isocyanate polyurea according to claim 1, wherein in step (2), the reaction temperature is 150-190°C, the reaction pressure is 10.6-23.5 MPa, and the reaction time is 6-11 hours.
14. A non-isocyanate polyurea prepared according to the method according to any one of claims 1 to 13.
15. The non-isocyanate polyurea of claim 14, wherein the non-isocyanate polyurea is an amine-terminated linear polymer.
16. The non-isocyanate polyurea of claim 14, wherein the non-isocyanate polyurea is an amine-terminated branched polymer.
17. A method for preparing a water-based non-isocyanate polyurea, the method comprising the following steps: (1) preparing non-isocyanate polyurea according to the method according to any one of claims 1 to 13; (2) Under dispersion conditions, an emulsifier is added to the non-isocyanate polyurea prepared in step (1), and then water is slowly added to obtain a water-based non-isocyanate polyurea.
18. The method for preparing water-based non-isocyanate polyurea according to claim 17, wherein the emulsifier is a polyoxyethylene ether emulsifier.
19. The method for preparing water-based non-isocyanate polyurea according to claim 17, wherein the amount of the emulsifier added is 2-10% by weight based on 100% by weight of the non-isocyanate polyurea.
20. The method for preparing a water-based non-isocyanate polyurea according to claim 17, wherein the ratio of the weight of the non-isocyanate polyurea to the weight of the added water is in the range of 1:1 to 1:
5.
21. A non-isocyanate polyurea anticorrosive coating, comprising: 50-80 parts by weight of the non-isocyanate polyurea prepared by the preparation method according to any one of claims 1 to 13, 10-30 parts by weight of titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoamer, 0.3-1.0 parts by weight of an ultraviolet absorber and 2-20 parts by weight of a solvent.
22. The non-isocyanate polyurea anticorrosive coating according to claim 21, wherein The titanium dioxide is rutile titanium dioxide; and / or The defoamer is a polyolefin solution defoamer; and / or The dispersant is a polyphosphate wetting dispersant; and / or The ultraviolet absorber is a benzotriazole ultraviolet absorber; and / or The solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate and xylene.
23. A non-isocyanate polyurea waterproof coating, comprising: 25-43 parts by weight of the non-isocyanate polyurea prepared according to the preparation method of any one of claims 1 to 13, 20-28 parts by weight of a plasticizer, 25-36 parts by weight of a filler, 0.1-0.5 parts by weight of a defoamer and 3-11 parts by weight of a solvent.
24. The non-isocyanate polyurea waterproof coating according to claim 23, wherein: The plasticizer is one or more of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, trioctyl phosphate, citrate and chlorinated paraffin plasticizers; and / or The filler is one or more of rutile titanium dioxide, kaolin, heavy calcium carbonate, barium sulfate, magnesium oxide, calcium oxide, wollastonite and talc; and / or The defoamer is a polyolefin solution defoamer; and / or The solvent is one or more of xylene, solvent oil, ethyl acetate, butyl acetate and propylene glycol methyl ether acetate.
25. A water-based non-isocyanate polyurea-based intumescent fire-retardant coating for steel structures, comprising: 25-35 parts by weight of a water-based non-isocyanate polyurea prepared by the preparation method according to any one of claims 17 to 20, 0.1-1 parts by weight of a defoamer, 0.5-1 parts by weight of a dispersant, 0.1-0.5 parts by weight of a pH regulator, 5-20 parts by weight of titanium dioxide, 6-15 parts by weight of melamine, 6-15 parts by weight of pentaerythritol, 20-30 parts by weight of ammonium polyphosphate, 0.3-1 parts by weight of a thickener and 10-25 parts by weight of water.
26. The water-based non-isocyanate polyurea-based intumescent fire retardant coating for steel structures according to claim 25, wherein: The defoamer is a composite silicone defoamer; and / or The dispersant is an aqueous solution of modified styrene maleic anhydride copolymer; and / or The pH regulator is an aqueous solution of reactive organosilicon; and / or The titanium dioxide is rutile titanium dioxide; and / or The thickener is a polyurethane modified polyether associative thickener.
27. A water-based non-isocyanate polyurea-based transparent finishing fire-retardant coating, which comprises: 25-35 parts by weight of water-based non-isocyanate polyurea prepared by the preparation method according to any one of claims 17 to 20, 0.1-1 parts by weight of a defoamer, 0.1-0.3 parts by weight of a pH adjuster, 8-15 parts by weight of a polyol, 20-30 parts by weight of ammonium polyphosphate, 8-15 parts by weight of a water-based amino resin, 0.5-1 parts by weight of a thickener and 10-25 parts by weight of water.
28. The water-based non-isocyanate polyurea-based transparent finishing type fire retardant coating according to claim 27, wherein: The defoamer is a composite silicone defoamer; and / or The pH regulator is an aqueous solution of reactive organosilicon; and / or The polyol is selected from one or more of sorbitol, xylitol and maltitol; and / or The ammonium polyphosphate is a short-chain low-polymerization ammonium polyphosphate that is completely soluble in water; and / or The water-based amino resin is a methyl etherified melamine amino resin; and / or The thickener is a polyurethane modified polyether associative thickener.